The Phenomenon Of Code Switching And Code Mixing In English Learning Classroom - Refi Rizki Radian; Pratomo Widodo; Erna Andriyanti (Britain International for Academic Research (BIAR) Publisher, 2023)
The diversity of languages in Indonesia has sundry errors such as gaps, errors in interpreting other languages, and others. It means, it also applies when in the process of learning foreign languages at school, especially English. Thus, learning English is difficult to build a positive spirit in learning, making students active and responsive in the learning process. Therefore, this study focuses on examining the types of code-switching and code-mixing in learning English in schools. This study uses a qualitative paradigm, using a descriptive case study type of research. Therefore, the researcher sets the goal to describe the data as it occurs in the phenomenon under study. This study is the occurrence of code-switching and code-mixing events in learning English at school. In this study, the researcher used guided semi structured interviewed as a data collection technique. The data from this study was analyzed based on the steps used, namely identifying the data, classifying the data, and describing the data according to the research objectives. The results of this study are the determinants of code-switching and code-mixing from teachers or students. Then, there are types of each between code-mixing and code-switching.